Invasive paediatric Elizabethkingia meningoseptica infections are best treated with a combination of piperacillin/tazobactam and trimethoprim/sulfamethoxazole or fluoroquinolone - Chan, Jaclyn Chi Lin (2021)
Objectives: Elizabethkingia meningoseptica is a multi-drug-resistant organism that is associated with high mortality and morbidity in newborn and immunocompromised patients. This study aimed to identify the best antimicrobial therapy for treating this infection. Methods: A retrospective descriptive study was conducted from 2010 to 2017 in a tertiary paediatric hospital in Singapore. Paediatric patients aged 0 to 18years old with a positive culture for E. meningoseptica from any sterile site were identified from the hospital laboratory database. The data collected included clinical characteristics, antimicrobial susceptibility and treatment, and clinical outcomes. Results: Thirteen cases were identified in this study. Combination therapy with piperacillin/tazobactam and trimethoprim/sulfamethoxazole or a fluoroquinolone resulted in a cure rate of 81.8 %. The mortality rate was 15.4 % and neurological morbidity in patients with bacteraemia and meningitis remained high (75%). Conclusions: Treatment with combination therapy of piperacillin/tazobactam and trimethoprim/sulfamethoxazole or a fluroquinolone was effective in this study, with low mortality rates being observed.